(untitled) (Biological Sciences - PJSIR, 2008)
In the investigation of 40 different vegetable growing farms of Al-Batinah (Oman) and Al - Ain (UAE) regions different pesticide residues were found to be present on all soil samples which varied in their types and levels according to the region. In Omani soil samples, cypermethrin was the most frequent pesticide, followed by chlorpyrifos, malathion, phenthoate, triazophos and deltamethrin. In UAE farm soil samples, chlorpyrifos, cypermethrin and deltamethrin were detected in all the regions, while phenthoate was detected in the Eastern and Northern regions only.